PENERAPAN PERAMPASAN ASET SEBAGAI PIDANA TAMBAHAN DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA - Rosalinda Jati (Universitas Semarang, 2021)
Confiscation of assets is a form of eradication in reducing the number of corruption crimes in Indonesia, the provisions of which are in the Criminal Code (KUHP) regarding additional crimes. The application of confiscation of assets has been carried out in many cases of corruption but the amount of assets seized tends to be incompatible with or ommensurate with the amount of state financial losses that have been corrupted. In this study, the focus is on the application of confiscation of assets in the eradication of Corruption Crime in Indonesia and ideally setting the confiscation of assets in the eradication of Corruption in the future. Normative legal research is a type of research used by the author. To obtain the results of the research carried out by qualitative analysis. The problem approach used by the writer in conducting this research is an invitation-friendly approach and a case approach. This research is indispensable because it provides a new building for eradicating corruption using methods that monitor money and follow the track record of corruption resulting from corruption. The next stage is by seizing wealth, the assets which are seized are known to be a criminal act committed by a crime that cannot feel the crime that was committed. The method of proof is deemed easier, because the concept of loading proof is reversed.